2015
DOI: 10.3109/09638288.2015.1052575
|View full text |Cite
|
Sign up to set email alerts
|

Using different methods to communicate: how adults with severe acquired communication difficulties make decisions about the communication methods they use and how they experience them

Abstract: Adults with acquired communication difficulties find digital communication, such as e-mail and social media, and mainstream technologies, such as iPads, beneficial in communicating with others. Current communication technologies present a number of challenges for adults with disabilities and are limited in their communicative functions to support desired interactions. The implications for AAC technology development and speech and language therapy service delivery are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
0
28
0
3
Order By: Relevance
“…Paterson et al (2015) reported that people with acquired conditions who use AAC were often frustrated with AAC technologies, reporting that they had limited functional interactions using these systems. In contrast, they experienced mainstream technologies and digital communications, like social media, to be beneficial when communicating with other people [75]. Communicating in digital environments also appeared to assist in re-establishing self-identity in individuals with acquired communication impairments [75].…”
Section: Augmentative and Alternative Communication (Aac) Technologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Paterson et al (2015) reported that people with acquired conditions who use AAC were often frustrated with AAC technologies, reporting that they had limited functional interactions using these systems. In contrast, they experienced mainstream technologies and digital communications, like social media, to be beneficial when communicating with other people [75]. Communicating in digital environments also appeared to assist in re-establishing self-identity in individuals with acquired communication impairments [75].…”
Section: Augmentative and Alternative Communication (Aac) Technologiesmentioning
confidence: 99%
“…User preferences were observed to include the desire for AAC systems and software to be consistent in access and performance, and easy to install and use [46]. Paterson et al (2015) reported that people with acquired conditions who use AAC were often frustrated with AAC technologies, reporting that they had limited functional interactions using these systems. In contrast, they experienced mainstream technologies and digital communications, like social media, to be beneficial when communicating with other people [75].…”
Section: Augmentative and Alternative Communication (Aac) Technologiesmentioning
confidence: 99%
See 3 more Smart Citations